Analysis of students' perception of virtual teaching of Physical Sciences at the Universidad Nacional Mayor de San Marcos - Castillo, Miguel (2021)
This work, has allowed us to process and analyze the data obtained about the perception of students in the face of the virtual teaching of physical sciences in the academic system of university training at this stage of pandemic, product of the Covid-19; the system of education under the health emergency was abruptly changed from the modality of classical face-to-face education to a new mode of virtual education. For this work, around 100 students were surveyed basic science faculties such as Physical Sciences and Biological Sciences, as well as the Professional School of Education and the Professional School of Education and the Professional School of Electrical Engineering of the National University of San Marcos, this survey was conducted at the end of the 2020-I semester. A survey form was applied with 16 questions to be answered by students, those questions were regarding: 1. Training, technical equipment and the internet. 2. Teachers and their methodology applied. 3. Teaching resources. Of the results obtained on: trainings, technical teams and the internet a large percentage (59.6 %) of the students surveyed stated that they do not need the trainings because they know the topic of virtual classrooms and their digital tools, most students surveyed (67 %) they manifest themselves to have their own computer electronic equipment to develop their virtual classes. On teachers and their methodology, students said it was good (31.9 %); in the face of the evaluation system they have pointed out that it was also good (54.3 %). About the teachers and their applied methodology, the students expressed their satisfaction (37.2 %), they also rated the teacher as regular (30.9 %) during this stage of the virtual classes. About didactic resources, 75.5 % of students stated that they had used didactic resources, a representative group of students (43.6 %) stated that teachers dominate the use of digital resources and materials for virtual classes, as well as A majority group of students (51.1 %) stated that the resources and materials used by the teachers have served for the teaching-learning of virtual classes.